Primary Sclerosing Encapsulating Peritonitis in an Adult Male: A Case Report - Haydar, M.D., Alaa; Kaouk, M.D., Hussein; Sawaya, M.D., Zeina; Saliba, Marita; Ibrahim, Reina; Tayar, M.D., Claude (International Journal of Innovative Research in Medical Science, 2022)
Introduction: Primary sclerosing encapsulating peritonitis (PSEP), also referred to as “cocoon abdomen”, is a rare but potentially devastating disease. It is defined as the encapsulation of a segment of the small bowel by a fibro-collagenous membrane leading to acute or sub-acute small bowel obstruction. Though the exact etiology and pathophysiology of this debilitating medical condition are still controversial, PSEP has been reported to be associated with multiple congenital developmental abnormalities. Diagnosis of PSEP is usually delayed as the disease is relatively rare and commonly present with non-specific symptoms associated with non-specific laboratory findings and non-conclusive radiologic features. Patient Concerns: We present a 42-year-old male patient presenting for elective abdominal laparoscopy for his four-year recurrent abdominal pain. Diagnosis: Preoperative diagnosis of PSEP as the cause of his chronic abdominal pain was not made until at laparotomy where a thick fibrotic peritoneal sac encasing the entire small bowel was found. Interventions: Excision of the fibrotic sac with extensive adhesiolysis were done by the general surgeon. Outcomes: The patient experienced a ten-day period of post op ileus after which he had a complete recovery. Conclusion: With the increasing number of cases suffering from this condition being reported in literature, surgeons must be aware of this debilitating disease in the differential diagnosis of abdominal obstruction.